2020
DOI: 10.3390/cancers12113225
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Acute Myeloid Leukemia: Recently Approved Therapies and Drugs in Development

Abstract: Acute myeloid leukemia (AML) is a genetically heterogeneous malignancy comprised of various cytogenetic and molecular abnormalities that has notoriously been difficult to treat with an overall poor prognosis. For decades, treatment options were limited to either intensive chemotherapy with anthracycline and cytarabine-based regimens (7 + 3) or lower intensity regimens including hypomethylating agents or low dose cytarabine, followed by either allogeneic stem cell transplant or consolidation chemotherapy. Fortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 102 publications
0
45
0
Order By: Relevance
“…[1][2][3][4][5][6] Antibodydrug conjugates (ADCs), comprising monoclonal antibodies conjugated to cytotoxic agents (payloads) via a linker, have emerged as novel therapeutic options. [7][8][9][10] ADCs have been approved for the treatment of metastatic urothelial cancer (mUC), metastatic breast cancer, and hematological malignancies, [11][12][13][14][15][16][17][18][19][20][21] and several are currently in clinical development. 7 They represent significant progress for the treatment of advanced cancers, as ADCs offer tumor specificity and potency not achievable with traditional therapeutic options while limiting the toxicity associated with an unconjugated payload.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Antibodydrug conjugates (ADCs), comprising monoclonal antibodies conjugated to cytotoxic agents (payloads) via a linker, have emerged as novel therapeutic options. [7][8][9][10] ADCs have been approved for the treatment of metastatic urothelial cancer (mUC), metastatic breast cancer, and hematological malignancies, [11][12][13][14][15][16][17][18][19][20][21] and several are currently in clinical development. 7 They represent significant progress for the treatment of advanced cancers, as ADCs offer tumor specificity and potency not achievable with traditional therapeutic options while limiting the toxicity associated with an unconjugated payload.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference in the survival analysis of GNA15 expression in the entire cohort, which may be caused by the complicated prognostic analysis of AML. For example, the application of hematopoietic stem cell transplantation, targeted drugs and immunotherapy could greatly improve the prognosis of high-risk patients ( 24 , 25 ). Therefore, we further performed the prognostic analysis in adult AML with normal karyotype and found that high GNA15 expression was independently associated with poor OS and RFS in this subgroup, which was consistent with the survival analysis results of the GEO database.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of targetable AML-specific surface markers, driver oncogenes and cellular pathways finally led to the development of new effective treatments; see Figure 1 [132,133] In the last few years, six new drugs have been approved by the U.S. Food and Drug Administration (FDA) for the treatment of newly diagnosed or relapsed or refractory (R/R) AML in UNFIT patients: the FLT3 inhibitor gilteritinib, the IDH inhibitors ivosidenib and enasidenib, the anti-CD33 monoclonal antibody gemtuzumab ozogamicin, the hedgehog pathway inhibitor glasdegib and the BCL-2 inhibitor venetoclax [10]. In this new context, a detailed genetic characterization of the disease with early identification of targetable mutations has become essential.…”
Section: Less-intensive Approachesmentioning
confidence: 99%